"It's in the Air"—Sponsored Editorial Content as a Path for Stealth Government Propaganda: The Case of Israeli Media. Issue 7 (16th September 2021) - Balint, Anat
Abstract: This article explores the rise of government-sponsored content, a recent development in the branded content model, in which government agencies assume the role of sponsors of editorial content. Theoretically, branded content blurs the boundary between strategic messages and communicative ones. As such, it embodies an inherently manipulative essence. By examining three case studies of government-sponsored content deals in the Israeli market (2014, 2016, 2017), the article seeks to understand the implications of such blurring once government agencies adopt this practice. Based on triangulation of sources (government documents, media content and reports in the press) the study follows the formation of these deals and dissects the consequences of their implementation. Findings suggest that government-sponsored content promotes the infliction of new types of harm that differ from those customarily associated with commercial sponsorship. It impels media bodies to adopt the role of government agencies at the formation stage. Subsequently, it allows these government campaigns to establish a ubiquitous presence within media space. Most important, the deals open a path for stealth propaganda, either for personal promotion of politicians or advancement of political agendas concerning controversial topics. As such, they corrupt both media outlets and the public sector.